Analysis of Air Induction System Testing on the 2011 Daihatsu Xenia Type Xi - Bahtiar Wilantara; Hamid Nasrullah; Muhamad Abdul Rois (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2023)
Analysis of this air induction system testing aims to analyze the air induction system on Daihatsu Xenia types XI in 2011. The research uses descriptive methods by testing and analyzing Daihatsu Xenia Type XI Mobils in 2011 using the EFI X 431 Pro and multitester scanner to obtain research data. The test results show that: 1. The sensor map is in good condition because the voltage produced ? 3.5 V - 4 V is: 3.7 V. 2. The sensor is in poor condition because the resistance produced is ? 2.21 k ohm - 2,69 K Ohm, namely: 1.74 KOHM. 3. ISC in poor condition because the resistance produced ? 45.6 ohms - 50.4 ohms is: 43.2 ohms. Testing using Scantool Obtained Results: 1. Map sensor has decreased at rpm 2000 of 2 kPa and has increased in rpm 3000 of 2 kPa. 2. IAT Sensors at 1000, 2000 and 3000 RPMs are stable at 480C. 3. ISC at rpm 1000, 2000, and 3000 stable at 6.99 %.